Meningkatkan Penguasaan Kosa Kata dengan Metode Mimicry Memorization: Studi Kasus MIN 4 Jombang - Hidayatulloh, Uzair Hasan; Afiffudin, Moch. Anang; Huda, Hisbullah (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study examines the effectiveness of the Mimicry Memorization (Mim-Mem) method in improving Arabic vocabulary (mufradat) mastery among fourth-grade students at MIN 4 Jombang. The research aims to address vocabulary acquisition challenges by exploring how repetition and imitation in Mim-Mem enhance mastery and student engagement.Method – This study employs a quantitative approach with a Nonequivalent Control Group Design. A total of 58 students were divided into experimental (28 students) and control (30 students) groups. Pre-test and post-test assessments measured oral performance in pronunciation, confidence, word choice, and response speed. Data were analyzed using Mann-Whitney and Student t-tests. Findings – The experimental group using Mim-Mem achieved an average score of 91.43, significantly higher than the control group’s 70.33 (p < 0.001). The method effectively improved pronunciation, confidence, word selection, and response speed, with a strong effect size (Cohen’s d = 4.755). These improvements indicate that Mim-Mem facilitates deeper retention and faster recall of vocabulary through structured repetition and active engagement. Additionally, students in the experimental group showed increased enthusiasm and participation in learning activities, suggesting that the method not only enhances cognitive retention but also fosters a more interactive and enjoyable learning environment. Research Implications – The study confirms the effectiveness of Mim-Mem in enhancing vocabulary mastery among elementary students. While limited to a specific context, the findings highlight the benefits of repetition-based learning with immediate feedback. Educators are encouraged to adopt and refine this method, while future research should explore its long-term impact and application in other languages and curricula.